Cyteen - Cherryh, C. J. (Warner Books, 1988)
The powers-that-be on the capital world of Union clone the murdered power broker, scientist Ariane Emory, but the new, headstrong Ariane knows the plans of her would-be controllers
60144
Keywords: Science fiction